Work domain analysis of driving information - Alm, Håkan; Davidsson, Staffan; Birell, Stewart; Young, Mark (Luleå tekniska universitet, Arbetsvetenskap, 2009)
In order to drive in a safe and environmentally friendly manner a driver needs support on the skillbased, rule based and knowledge based level (Rasmussen, 1986). It can be argued that today's driverinformation mainly supports skill and rule based levels while the complex task of driving also needssupport on the knowledge based level, e.g. problem solving . The aim of this study was to identifyways to support problem solving and decision making in a driving information context and to studygaps, overlaps, strong and weak relations between the driver information functions and the purpose ofthe functions.Work Domain Analysis (WDA) (Vicente, 1999) was used to decompose the purpose of the driverinformation down to the component level. WDA is the first step of five in Cognitive Work Analysis(CWA). CWA belongs to the category of Ecological Interface Design that aims to aid the design ofhuman centred interfaces and systems that support problem solving and decision making in complexsocio-technical systems.The study was performed by researchers from Luleå University of Technology and Volvo Cars as wellas members of a Driving information project. The study was limited to driver information systems inprivate cars which means that the main purpose of the systems was to support drivers' goals e.g.navigate or maintain speed but also being environment friendly, etc. It should also be mentioned thatdriver information not only was limited to information within the car. Before and after driving was alsoincluded. The WDA identified five functional purposes of driving information: To support safe,efficient, environment friendly, legal and enjoyable transportation.The "Functional purpose" was decomposed into "abstract functions" e.g. support choice oftransportation, reduce energy exposure, improve friction, and maintain lateral and longitudinal distance.Further decomposition down to "physical form" showed several weak and some unexpected relationsbetween the purpose and the system. For instance, one conclusion was that the relation ...